THE INFLUENCE OF THE SCHOOL OF IGOR ALEXANDROVICH MOJSEYEV IN THE MACEDONIAN FOLK DANCE ENSEMBLE - Kostov, Stojance (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
The topic of this paper is the impact of the Russian school of the famous ballet dancer and choreographer Igor Alexandrovich Mojsejev in amateur ensembles in Macedonia and in the only professional ensemble of Macedonian folk dances and songs -the ensemble “Tanec”. This influence begins about in the fifties of the twentieth century, causing big changes in the manner of the stage presentation of folklore and is an interesting phenomenon for research that still endures today. Keywords: stage presentation, folklore, Russian school, folk dances.